Synergistic effect of UV-C irradiation and high-pressure processing in reducing microbial load in “Nanglae” pineapple juice compared to conventional heat treatment - Suthiluk, Phunsiri; Chuensombat, Nuntawan; Setha, Sutthiwal; Naradisorn, Matchima (Frontiers in Sustainable Food Systems, 2023)
Thermal processing is widely used in juice production to ensure microbial safety and to extend juice shelf life; however, it can have an impact on quality attributes such as color and nutritional content. UV-C irradiation and high-pressure processing (HPP) are non-thermal processing methods which causes little impact on the quality of fruit juice compared to conventional heat treatment (CHT). The objective of this study was to investigate the effect of combining UV-C and HPP (UV-C + HPP) treatments on microbial loads and quality of ‘Nanglae’ pineapple juice during cold storage at 5 ± 1 ℃ for 91 days. The treatments were as follows: (1) no treatment; (2) conventional heat treatment (80 ± 5 ℃, 10 min); and (3) a combination of UV-C (3 kJ/m2) and HPP (600 MPa, 5 min) treatments. The combined treatments of UV-C and HPP reduced the numbers of viable cells of aerobic microorganisms to less than the quantification limit of 1.48 log CFU/mL and yeasts and molds to less than 1.18 log CFU/mL throughout the 91-day storage period. Pineapple juice treated with CHT contained yeasts and molds exceeding the quantification limit of 1.18 log CFU/mL after 63 days of storage. The UV-C + HPP treatment preserved carotenoids and protein levels comparable to those found in fresh pineapple juice over 91 days of storage, whereas the CHT significantly decreased these values. Throughout the storage period, ascorbic acid levels in the CHT were slightly lower than in the combined treatments. These results clearly demonstrate that the combination of UV-C and HPP can ensure the safety of ‘Nanglae’ pineapple juice while also retaining bioactive compounds. Combining these two technologies could be a new approach to producing healthy and safe juices.